Why desk rejections happen and how young researchers can avoid them: Practical lessons from experience - Zerfu, Taddese Alemu (ECR Life, 2025)
Publishing our work is a critical part of an ECR’s journey. Papers are not always sent out for revision, and it can be discouraging for ECRs to face desk rejections. Here, Dr. Taddese Zerfu shares his insights on how to minimize the chances of facing a desk rejection.